The Inception and Formation of the Theory of Hyperfiltration Through the Ages (Iranian Journal of Kidney Diseases, 2012)
With the rising incidence of metabolic syndrome and progressive kidney disease, efforts to halt this progression have become the mainstay of therapies in the era of modern nephrology. The necessity of one versus two kidneys has occupied the minds of leading scientists and philosophers throughout the ages and has laid the foundation for our understanding of progressive kidney disease. This review focuses on the major discoveries of the leading thinkers who with their paradigm shifting ideas and skepticism pushed the boundaries of our knowledge and shaped the theory of hyperfiltration.